Secret Of The Truth In Mike Newell's Prince Of Persia Movie (2010): An Existentialist Approach - Artanti, Catur Dwi (2012)
This study is about secret of the truth in Prince of Persia movie (2010). The objective of this study is to apply the Existentialist approach to analyze the secret of the truth in Prince of Persia. The writer uses Sartre's major point of Existentialism to answer the problem of the study. The researcher uses qualitative research. The data of the study is image and text taken from two data sources. The primary source is Prince of Persia movie itself directed by Mike Newell, released in 2010. While the secondary data source are from other materials taken from book, internet, and journal which related to the study. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity. Second, based on the existentialist analysis, human have different existence. Its existence is based on different being, choice, and act. Human has a freedom to choose and then responsible for his existence. The responsibility will result an anxiety. Mike Newell wants to convey a moral message that human should tell the truth whatever the risks. If the secret of the truth should be kept, it would be taken responsibility not only for himself but also for the whole humanity.